Transboundary Spread of Brucella canis through Import of Infected Dogs, the Netherlands, November 2016–December 2018 - van Dijk, Marloes A.M. (Emerg Infect Dis, 2021)
Brucella canis had not been isolated in the Netherlands until November 2016, when it was isolated from a dog imported from Romania. Including this case, 16 suspected cases were notified to the authorities during the following 25 months. Of these 16 dogs, 10 were seropositive; tracking investigations found another 8 seropositive littermates. All seropositive animals were rescue dogs imported from Eastern Europe. B. canis was cultured from urine, blood, and other specimens collected from the dogs. Genotyping of isolates revealed clustering by litter and country. Isolating B. canis in urine indicates that shedding should be considered when assessing the risk for zoonotic transmission. This case series proves introduction of B. canis into a country to which it is not endemic through import of infected dogs from B. canis–endemic areas, posing a threat to the naive autochthonous dog population and humans.